Pengembangan Media Pembelajaran Berbasis Videoscribe pada Materi IPS Pokok Bahasan Gejala Alam di Indonesia dan Negara Tetangga Kelas Vi Sekolah Dasar - Rahmadani, Ginta Prastya; Wahyudi , Wahyudi; Sahari, Sutrisno (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research aims to develop from research to produce product development of videoscribe-based learning media social studies subject matter of natural phenomena in Indonesia and neighboring class countries. This research method uses the R&D (Research and Development) method with the ADDIE model which consists of (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation stages. The subjects in this study were teachers and students of class VI at SD Negeri 3 Besole, Besuki District, Tulungagung Regency. There were two trial designs that were carried out, consisting of a limited trial on 8 students and a large trial on 28 students. The conclusions of this study are (1) Videoscribe media can be said to be valid and suitable for use as learning media by obtaining validation carried out by media expert validators obtaining a percentage of 95%, while material validators obtain a percentage of 97.7%. (2) Videoscribe media can be said to be practical and appropriate for use in learning by obtaining a percentage score of 98%. While the response of class VI students to videoscribe media obtained a score percentage of 92.8%. (3) Videoscribe media can be declared effective in the learning process. with mastery learning to get a value of 88%. Meanwhile, for the wide trial, it obtained an average score of 96 and exceeded the KKM score (75) with the percentage of learning completeness obtaining a score of 100%.